2021
DOI: 10.1177/23409444211063889
|View full text |Cite
|
Sign up to set email alerts
|

Family firm heterogeneity on CSR approach: A socio-emotional (SEW) perspective

Abstract: How family firms adopt a certain corporate social responsibility (CSR) approach remains a relatively unexplored matter in family firm and firm ethics research. Hence, we study how and why the CSR approach (broad vs. narrow; benefits vs. costs) differs within family firms, addressing the influence of the socio-emotional wealth (SEW) dimensions, individually or combined. We used empirical evidence gathered through 13 case studies of firms from the Andalusia region and we used the interpretative approach of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…The fact that we find a slightly negative effect on one CSR dimension when exchanging firm tradition by family stage adds to this contradictory pictures. This could be an indication that firm tradition overlaps with other dimensions of SEW, such as identification or emotional attachment: Depending on how much the managing family member identifies with the strategic approach of preceding generations, firm tradition might factor in or not, as Dieguez-Soto et al (2021) observe in their qualitative study. We therefore propose future research to investigate the phenomenon more in depth to identify possible moderating or mediating effects in the interplay of family firm tradition and SEW.…”
Section: Discussion and Limitations Of The Studymentioning
confidence: 96%
“…The fact that we find a slightly negative effect on one CSR dimension when exchanging firm tradition by family stage adds to this contradictory pictures. This could be an indication that firm tradition overlaps with other dimensions of SEW, such as identification or emotional attachment: Depending on how much the managing family member identifies with the strategic approach of preceding generations, firm tradition might factor in or not, as Dieguez-Soto et al (2021) observe in their qualitative study. We therefore propose future research to investigate the phenomenon more in depth to identify possible moderating or mediating effects in the interplay of family firm tradition and SEW.…”
Section: Discussion and Limitations Of The Studymentioning
confidence: 96%
“…Besides the firm economic goal, the owners of family firms also search for preservation of socioemotional wealth as non-economic reward from their business (Glover & Reay, 2015). Dieguez-Soto et al (2021) and Berrone et al (2012) stated that socioemotional wealth is considered as a unique differentiator that might explain non-identical characteristics of most family firms, exhibiting non-similar behavior and interests. It allows incorporation between firm and family that unfold fundamentals in strategic decision-making (Araya-Castillo et al, 2021).…”
Section: Literature Review Socioemotional Wealth As Distinctive Eleme...mentioning
confidence: 99%
“…Moreover, at least here, the 'family control' prediction of SEW aligns with the 'women prioritize family interests' prediction of interdependent self-construal theory. Further research has shown that family firms are heterogeneous with respect to SEW and that, as a result, family firms are heterogeneous in their approach to CSR (e.g., Diéguez-Soto et al, 2021). Indeed, research is taking a more nuanced view of the SEW construct itself, following Kellermanns et al's (2012) argument that the SEW dimensions can be positively and negatively valenced.…”
Section: Sustainability/csrmentioning
confidence: 99%